Partial cutting in mixedwood stands: Effects of treatment configuration and intensity on stand structure, regeneration, and tree mortality. (3rd April 2019) - Lafleur, Benoit; Harvey, Brian D.; Mazerolle, Marc J.
ABSTRACT: In temperate and boreal mixedwood forests of eastern North America, partial disturbances such as insect outbreaks and gap dynamics result in the development of irregular forest structures. From a forest ecosystem management perspective, management of these forests should therefore include silvicultural regimes that incorporate medium- to high-retention harvesting. We present 12-year results of a field experiment undertaken to evaluate the effects of variable retention harvesting on stand structure, recruitment, and mortality. Treatments were gap harvesting (GAP), diameter-limit harvesting (DL), careful logging (CL), and careful logging followed by scarification (CL + SCAR), and an unharvested control. Although post-harvest basal area in the GAP treatment was significantly lower than that of controls, it maintained a diameter distribution profile and densities of balsam fir regeneration similar to those of pre-harvest conditions. Lower retention treatments (DL, CL, and CL + SCAR) tended to favor regeneration of pioneer, shade-intolerant species. Except for black spruce (for which mortality was highest in DL), stem mortality was similar among harvesting treatments. From an ecosystem management perspective, this study suggests that gap harvesting can maintain, in the short term, forest stand composition and structure similar to unharvested forests, and could be used where management objectives include the maintenance of late successional forest conditions.